Pengaruh Video Edukasi Self Care terhadap Pengetahuan dan Motivasi Kepatuhan Antiretroviral (ARV) Orang dengan HIV (ODHIV) - Zyarohtul Wildan Navilda; Ahmad Ikhlasul Amal (Quantum Wellness : Jurnal Ilmu Kesehatan, 2025)
Background: HIV is a virus that targets the human immune system. It can spread through sperm or vaginal fluid during intercourse, needles from infected individuals, or blood. The virus is more accurately known as a syndrome, which is a group of symptoms from different illnesses and infections. The term ODHIV (People with HIV) refers to individuals who are infected with HIV. Objective: To determine the effect of self-care educational videos on the knowledge and motivation of antiretroviral (ARV) adherence for people living with HIV (PLHIV). Method: The research uses a quantitative type of research with one group pre-post test design experiment. The sample consisted of 76 respondents. Sampling was determined using the Lemeshow formula technique. The data obtained were analyzed by using the Mann-Whitney test. Result: The results of the Mann-Whitney test means that there is an influence in providing knowledge and motivation for antiretroviral adherence in educational videos about HIV. Conclusion: There is an influence of self-care educational videos on the knowledge and motivation of antiretroviral (ARV) adherence for people living with HIV (PLHIV).